Myelin oligodendrocyte glycoprotein antibody-associated isolated aseptic meningitis: a single−center pediatric case series - Liu, Kang; Sun, Suzhen; Chen, Fang; Wu, Wenjuan; Li, Xin; Pang, Lingyu; Wang, Wei (Frontiers in Immunology, 2025)
Background and purposeAseptic meningitis represents a rare and underrecognized phenotype of myelin oligodendrocyte glycoprotein (MOG) antibody-associated disease (MOGAD). Despite sporadic case reports, comprehensive series studies remain scarce. This study aimed to describe the clinical characteristics of MOG antibody-associated aseptic meningitis (MOGAM) in pediatric patients without neuroparenchymal lesions.MethodsWe reviewed the medical records of pediatric patients from January 2019 to July 2025, focusing on cases diagnosed with MOGAM in the absence of neuroparenchymal lesions. Clinical manifestations, brain magnetic resonance imaging (MRI) findings, laboratory results, treatment regimens, and clinical outcomes were retrospectively analyzed.ResultsAmong 159 children with seropositive MOG antibodies, 11 (6.9%) met the inclusion criteria. The mean age at disease onset was 8.3 years (8.3 ± 3.2 years), with a male-to-female ratio of 5:6. The most common symptoms were fever (10/11), lasting from 3 to 50 days (median, 13 days; interquartile range [IQR], 8.0–22.7 days), and headache (10/11). Meningeal irritation signs were positive in 4 patients (4/11). Nine patients had peripheral blood leukocytosis (21.6 ± 3.6×109/L; range, 17.2–29.1×109/L), and 10 had elevated neutrophil-to-lymphocyte ratio (NLR; median, 4.5; IQR, 4.0–7.9; range, 3.0–14.5) as well as erythrocyte sedimentation rate (ESR; 38.4 ± 10.7 mm/h; range, 25–62 mm/h). All patients had cerebrospinal fluid (CSF) pleocytosis (117.4 ± 62.0/μL; range, 50–201/µL); 2 had elevated CSF pressure (range, 250–350 mmH2O); 4 had slightly increased CSF protein levels (range, 0.48–0.96 g/L); and none tested positive for infectious pathogens. Six patients showed abnormal electroencephalogram (EEG) results, including focal interictal epileptiform discharges or slow waves (3/6) and slow background activities (5/6). Brain MRI showed linear hyperintense signals along the bilateral cerebral sulci on fluid-attenuated inversion recovery (FLAIR) sequences in 4 patients (4/11), while no abnormalities were observed in 7 patients (7/11). Leptomeningeal enhancement (LME) was detected in 2 of 3 patients who underwent contrast-enhanced brain MRI. All patients received immunotherapy, with 2 administered immunosuppressive therapy after relapse. At the last follow-up, all patients achieved favorable clinical outcomes.ConclusionMyelin oligodendrocyte glycoprotein antibody-associated isolated aseptic meningitis is a novel and underrecognized clinical phenotype. For pediatric patients presenting with prolonged or recurrent fever and headache, particularly those with CSF pleocytosis, leptomeningeal enhancement (LME), and poor response to anti-infective therapy, early testing for MOG-IgG is strongly recommended. Timely identification of this distinct phenotype may facilitate early diagnosis, initiation of effective immunotherapy, and better clinical outcomes.